Analysis of Symptoms of Sick Building Syndrome for Nurses in Hospital Inpatient Rooms - Endang Purnawati Rahayu; Riri Maharani; Doni Jepisah; Ade Idra Suhara (Jurnal Penelitian Pendidikan IPA, 2023)
Sick Building syndrome is a symptom that is felt by someone who carries out activities in the building caused by poor indoor air quality conditions that can cause several symptoms of health problems. The purpose of this study was to analyze complaints of sick building syndrome among nurses in hospital inpatient rooms. This research method uses quantitative methods with analytic survey types. The design used was a cross-sectional study with a total sample of 120 people. Data analysis used the chi-square test. The results of this study showed that as many as 40% of nurses experienced symptoms of sick-building syndrome with the most common complaints being sneezing, runny nose/flu, dry skin, dry lips, and feeling tired. And the factors associated with the symptoms of sick building syndrome in nurses are temperature, humidity, lighting, occupancy density, air circulation, years of service, and age. So that hospital management needs to periodically check the physical environment in hospital inpatient rooms.